2022
DOI: 10.3389/frobt.2022.926185
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Matters: The Effect of Touching the Social Robot PARO on Pain and Stress is Stronger When Turned ON vs. OFF

Abstract: Social touch between humans, as well as between humans and animals, was previously found to reduce pain and stress. We previously reported that touching a social robot can also induce a reduction in pain ratings. However, it is unclear if the effect that touching a robot has on pain perception is due to its appearance and its pleasant touch, or due to its ability to socially interact with humans. In the current experiment, we aimed to assess the contribution of the interactive quality to pain perception. We as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…Previous studies have found that human touch can alleviate pain and stress when experiencing thermal pain [32] and reduce anxiety during cataract surgery [25]. Crucially, unlike the current study, both studies use adult subjects.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have found that human touch can alleviate pain and stress when experiencing thermal pain [32] and reduce anxiety during cataract surgery [25]. Crucially, unlike the current study, both studies use adult subjects.…”
Section: Discussionmentioning
confidence: 90%
“…We would submit that responsivity is a key phenomenon for human-robot interaction, too, when therapy, for Waldenfels, "responds by getting the other to respond" (Waldenfels 2020, p. 203)-which is a stated goal in the case of, for example, pet robots for patients with dementia. Indeed, it is evident that when robots are perceived as responsive, they have a stronger effect on the human user, be it a greater reduction in the perception of pain (Geva et al 2022), a decrease in salivary cortisol levels (Tanaka et al 2012), or an increase in prevalence of positive emotions (Crossmann et al 2018).…”
Section: Responsivity Virtual Responsivity and Constructed Responsive...mentioning
confidence: 99%
“…Several studies have shown that touching interactive robots provides emotional positive effects, such as reductions in pain and stress (Geva et al, 2020 , 2022 ). Besides, if such forms of the aforementioned skillful touch could be delivered by a robot, care receivers could have emotional positive effects and the lack of caregivers might be resolved (Eckstein et al, 2020 ; Sumioka et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%